Students' mathematical representation ability in Learning fractions through a concrete-representational-abstract approach with a joyful learning nuance - Fuad Nasir; Gunawan; Shanti Nurhidayah; Salsabila Anindiyah; Yudistira Indra Prahasta Putra Elwanda; Setiyani; Rahmad Khodari; Mohammad Dadan Sundawan; Laelasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Mathematical representation ability is crucial in understanding fraction concepts, especially for elementary school students still in the concrete cognitive development stage. This study aims to describe the mathematical representation abilities of fourth-grade students in learning fractions through the Concrete-Representational-Abstract (CRA) approach with a joyful learning atmosphere. This approach was implemented through educational games such as Run Speech Fraction, Jump and Draw Fraction, and Walk Fast Fraction. The study employed a descriptive qualitative method, involving three fourth-grade students from an elementary school in Cirebon, each representing a high, medium, and low ability level. Data were collected through written tests and in-depth interviews, and analysed using the Miles and Huberman model. The results indicate that when delivered in an engaging and enjoyable atmosphere, the CRA approach effectively supports the gradual development of verbal, visual, and symbolic representations. High-ability students demonstrated consistency across all three forms of representation; medium-ability students showed basic understanding but still required guidance; low-ability students faced difficulties yet remained enthusiastic throughout the learning process. This study contributes to developing instructional strategies that promote gradual conceptual understanding, foster enjoyable learning experiences, and encourage active student engagement in mathematics.